A Review of Research on Robotic Dexterous Hands - Liu Wei; Xiao Zhao; Qu Yinpeng; Xu Shouliang (Jixie chuandong)
Robot dexterous hand can mimic human movements to realize multiple tasks in complex scenarios, which is a key technology for developing intelligent humanoid robots. Focusing on the research history of robotic dexterity, the current research status of multi-fingered dexterity was elaborated, and the evolution process and research progress of dexterity were analyzed. The classification and characteristics of dexterous hands were discussed in terms of the number of degrees of freedom, drive mode, mechanical transmission mode and sensing technology, and the future development trend of dexterous hands was envisioned.